A New Look at the Determinants of Growth in Asian Countries - Ghazanchyan, Manuk (IMF Working Papers; Working Paper, 2015)
This study examines the drivers of growth in Asian countries, with focus on the role of investment, the exchange rate regime, financial risk, and capital account openness. We use a panel data set of a sample of Asian countries over the period 1980 to 2012. Our results indicate that private and public investments are strong drivers of growth, while more limited evidence is found that reduced financial risk and higher foreign direct investment support growth. The exchange rate regime does not appear to be a strongly significant determinant of growth, but some specifications suggest that more flexible regimes are beneficial in this respect. Financial crises have a stronger dampening effect on growth in countries with more open capital accounts.